Insights Into the Complexity of Craniofacial Development From a Cellular Perspective - Murillo-Rincón, Andrea P.; Kaucka, Marketa (Frontiers in Cell and Developmental Biology, 2020)
The head represents the most complex part of the body and a distinctive feature of the vertebrate body plan. This intricate structure is assembled during embryonic development in a four-dimensional process of morphogenesis. The head integrates components of the central and peripheral nervous system, sensory organs, muscles, joints, glands, and other specialized tissues in the framework of a complexly shaped skull. The anterior part of the head is referred to as the face, and a broad spectrum of facial shapes across vertebrate species enables different feeding strategies, communication styles, and diverse specialized functions. The face formation starts early during embryonic development and represents an enormously complex, multi-step process regulated on a genomic, molecular, and cellular level. In this review, we will discuss recent discoveries that revealed new aspects of facial morphogenesis from the time of the neural crest cell emergence till the formation of chondrocranium representing the primary design of the individual facial shape. We will focus on molecular mechanisms of cell fate specification, the role of individual and collective cell migration, the importance of dynamic and continuous cellular interactions, responses of cells and tissues to generated physical forces, and their morphogenetic outcomes. In the end, we will examine the spatiotemporal activity of signaling centers tightly regulating the release of signals inducing the formation of craniofacial skeletal elements. The existence of these centers and their regulation by enhancers represent one of the core morphogenetic mechanisms and might lay the foundations for intra- and inter-species facial variability.